Self-medicating in a difficult world - Monica Whyte (Murmurations)
To me, as a systemic family therapist working in the substance misuse field, it seems that family therapy has always had somewhat of a dilemma when it comes to working with family systems where there is a substance misuse disorder present. In this paper, I will be describing current thinking in family therapy practice within the substance misuse  field and how systemically informed substance misuse services are beginning to pay attention to issues of neurodiversity. Particularly concentrating on how adolescent (under 18) services are adapting to become more neuro-inclusive and neuro-affirmative. For substance misuse services, this is the opportune time to discuss and highlight the use of substances by the neurodivergent population. In this article, which is an elaboration on the presentation at the 4th Systemic Autism conference I outline changes that could be made to substance misuse treatment services to remove barriers to accessing substance misuse treatment that neurodivergent individuals may encounter when trying to change their relationship with substances.